Comparison between Rhabdomyolysis Induced and Septic Acute Kidney Injury in Central Nepal - Sedhain, Arun; Bhattarai, Gandhi Raj; Shrestha, Bidhan; Khan, Amir (Journal of Chitwan Medical College, 2019)
Background: Acute kidney injury (AKI) is one of the most serious complications of rhabdomyolysis (RM). We studied the clinical manifestations and prognosis of rhabdomyolysis induced AKI and compared it with septic AKI among hospitalized patients.Methods: A prospective study was conducted at Chitwan Medical College between January 2017 to June 2018 to compare AKI secondary to rhabdomyolysis (RM-AKI) and sepsis (SA-AKI). AKI was diagnosed as per Kidney Disease Improving Global Outcomes (KDIGO) 2012 guidelines. Rhabdomyolysis was diagnosed if serum creatinine phosphokinase raised >5 times the upper limit of normal level and sepsis as an increase of two or more points in the Sequential Organ failure Assessment (SOFA) score with the evidence of infection.Results: A total of 145 patients with AKI (21 with RM and 124 with sepsis) were included in the study. Mean age of the patients was 43.7 years with majority (54%) being males. Wasp bite and bee sting combined together (47.6%) were the most common causes for RM-AKI whereas pneumonia accounted for 46.6% of the septic AKI. Serum creatinine (SCr) at admission and at discharge were 3.8 and 1.4 mg/dL respectively in RM-AKI group; and 2.4 and 1.6 mg/dL in septic AKI group. Duration of stays in the hospital (9.2 versus 6.4 days) and ICU (4.2 versus 3.7 days) were longer in RM than in septic AKI. In hospital mortality was 4.8% in RM and 8.9% in septic AKI.Conclusions: This study has found that, despite a longer duration of hospital stay, RM-AKI had a lower in-hospital mortality than septic AKI.